Temperature and humidity monitoring and control of a poultry incubator - Tiong Li Hwa (School of Electrical System Engineering, University Malaysia Perlis, 2011)
This project discuss about the temperature and humidity monitoring and control of a poultry incubator. Temperature and humidity are the main parameter to the success of the incubator during the hatching process. To improve the hatchability and quality of the chicks, we can control the temperature and humidity inside the incubator to make sure the eggs is always in ideal condition. According to the research, the embryo will turn to a chick after twenty one days and will need different values of temperature and humidity on each day. Too high or too low of the temperature and humidity in the incubator will affect the development of the embryo. A circuit of temperature and humidity sensor is designed and put it inside the incubator so once abnormality value of temperature and humidity is detected, it can give action to solve the problem. PIC16F877A is used to store all the program and action of this project. A software named Proteous is used to pre-design the circuit of this project. However PIC C Compiler used to compile the code. After ensuring that the circuit is functional, the next step is to design PCB board for the circuit. Orcad is used to design and redraw a schematic diagram of the project just like the diagram drawn using Proteus. This schematic diagram will be needed in the process of designing the PCB board.